2014
DOI: 10.4236/nr.2014.511056
|View full text |Cite
|
Sign up to set email alerts
|

An Online mtDNA Tool for Identification of Neotropical Psittacid Species and Taxonomic Issues: A Study Case of the <i>Amazona ochrocephala</i> Complex

Abstract: Parrots are among the most popular pets in the world and they are also some of the most illegally traded, particularly in Brazil. Some computational tools were recently developed by researchers based on molecular databases for taxonomy support, forensic identification and conservation purposes. In this study, the DNA Surveillance platform was used to build an online database tool for molecular identification of Brazilian Psittacids using DNA sequences of six mitochondrial genes. To illustrate possible taxonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…H_14 contains the majority of COI’s from A. aestiva mitogenomes. The H9_clade1_SA, which is the haplotype closest to our sequence by the DNA Surveillance classification ( Figure 5 ), is part of clade 1, which according to Chaves et al (2014) , is related to the north-eastern group of Caparroz et al (2009) . The latter corresponds to the Brazil states Bahia, Tocantins, Minas Gerais, Distrito Federal, and Goiás.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…H_14 contains the majority of COI’s from A. aestiva mitogenomes. The H9_clade1_SA, which is the haplotype closest to our sequence by the DNA Surveillance classification ( Figure 5 ), is part of clade 1, which according to Chaves et al (2014) , is related to the north-eastern group of Caparroz et al (2009) . The latter corresponds to the Brazil states Bahia, Tocantins, Minas Gerais, Distrito Federal, and Goiás.…”
Section: Discussionmentioning
confidence: 80%
“…Previous molecular phylogenies have shown that A. aestiva and A. ochrocephala are not reciprocally monophyletic ( Eberhard et al , 2004 ; Ribas et al , 2007 ; Caparroz et al , 2009 ; Chaves et al , 2014 ). Also, the parents of the specimen whose mitogenome is being described here were apprehended from the illegal trade and their origin is unknown.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations